Citizen education and History. A teaching experiment at the Guillermo Rivera Cotapos high school in Viña del Mar - García Fernández, Gonzalo Andrés (Clio. History and History Teaching, 2021)
In this article we will present a teaching experiment performed in the context of a research on the formation of political and social perceptions through the teaching of History in schools. The experiment was carried out in an optional subject of Citizenship Education, where civic knowledge (laws, legal regulations, etc.) was usually taught. The purpose of this research experiment will be to analyze the educational context surrounding this subject and the students' perceptions of a radical formative paradigm shift. Finally, we will see how the “what” and the “how” of our teaching experiment will matter to us; how the development of historical thinking and imagination in the classroom generates greater cognitive freedoms than a rigorous and dogmatic knowledge of laws and regulations does, especially in the face of a more reflective and critical citizen training.
Keywords: civic and citizen education; historical thinking; student perceptions; school ethnography